SELECTION OF SUSTAINABLE DOMESTIC WASTE MANAGEMENT TECHNOLOGY CASE STUDY: TANJUNG MEKAR VILLAGE, KARAWANG - Nadia Paramita; Sari Sekar Ningrum (Journal of Community Based Environmental Engineering and Management, 2020)
The Citarum River is one of the rivers that is a source of clean water and is consumed by residents in the watershed and in DKI Jakarta. Currently, the Citarum River is facing serious environmental problems because it is a reservoir for waste from various sources such as factory, hotel and hospital waste as well as domestic waste, silting, problems with embankments and final treatment sites that are harmful to health. The results of monitoring the water quality of the Citarum River show that the water of the Citarum River has not been able to meet the water quality standards that have been determined based on the SK. West Java Governor No. 39 of 2000. The decline in water quality is caused by an increase in the pollutant load originating from the population, industrial development, extensification and intensification of agricultural land, fisheries development, livestock pollution and mining and excavation exploration. The focus of this research is emphasized on the river pollutant waste management program from domestic waste originating from community activities in Tanjung Mekar Village. The purpose of this study was to analyze waste management systems and domestic wastewater that are easily applied by the community, especially along rivers, in supporting community-based environmental management.